2019
DOI: 10.4037/ccn2019794
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Low Cardiac Output Syndrome at the Bedside: A Pediatric Cardiac Intensive Care Unit Survey

Abstract: BACKGROUND Low cardiac output syndrome is a transient constellation of signs and symptoms that indicate the heart’s inability to supply sufficient oxygen to tissues and end-organs to meet metabolic demand. Because the term lacks a standard clinical definition, the bedside diagnosis of this syndrome can be difficult. OBJECTIVE To evaluate concordance among pediatric cardiac intensive care unit nurses in their identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Or perhaps these could be explained by that patient receiving transannular patch likely has higher clinical risk factors like lower SpO2, so the statistical significance of which in relation to cardiovascular disorder might be unfortunately overshadowed by more significant covariates. 23 Our study has some potential limitations. Previous studies have suggested that altered transcriptomic regulation with regard to the development and progression of cardiovascular disorder in tetralogy of Fallot.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Or perhaps these could be explained by that patient receiving transannular patch likely has higher clinical risk factors like lower SpO2, so the statistical significance of which in relation to cardiovascular disorder might be unfortunately overshadowed by more significant covariates. 23 Our study has some potential limitations. Previous studies have suggested that altered transcriptomic regulation with regard to the development and progression of cardiovascular disorder in tetralogy of Fallot.…”
Section: Discussionmentioning
confidence: 88%
“…However, compared with other studies, our study did not observe any correlation between the presence of transannular patch and cardiovascular disorder. Or perhaps these could be explained by that patient receiving transannular patch likely has higher clinical risk factors like lower SpO2, so the statistical significance of which in relation to cardiovascular disorder might be unfortunately overshadowed by more significant covariates 23 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the incidence of LCOS after heart surgery can be as high as 25.16%. Although studies [ 12 , 13 ] have reported that the occurrence of LCOS may be related to preoperative cardiac function, intraoperative operations and CPB, there are still no exact indicators to reflect the risk of its occurrence. Therefore, exploring the risk factors of LCOS is of great significance to the prevention and treatment of LCOS after CHD in children.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, our multivariate analysis identified lower SpO2, lower pulmonary annular Z-score, and longer CPB time were independent risk factors of myocardial dysfunction. Consequently, understanding and accurately estimating perioperative risk by accounting for the intrinsic risk of surgical procedures and patient clinical characteristics will lead to a timely and accurate use of hemodynamic monitoring for a better identification and management of patients as risk for or in a state of myocardial dysfunction [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%